A Simple Flow Classification Parameter Can Discriminate Rupture Status in Intracranial Aneurysms. Issue 5 (18th May 2020) - Asgharzadeh, Hafez; Shahmohammadi, Ali; Varble, Nicole; Levy, Elad I; Meng, Hui; Borazjani, Iman
Abstract: BACKGROUND: A simple dimensionless aneurysm number (An ), which depends on geometry and flow pulsatility, was previously shown to distinguish the flow mode in intracranial aneurysms (IA): vortex mode with a dynamic vortex formation/evolution if An > 1, and cavity mode with a steady shear layer if An < 1 . OBJECTIVE: To hypothesize that An > 1 can distinguish rupture status because vortex mode is associated with high oscillatory shear index, which, in turn, is statistically associated with rupture. METHODS: The above hypothesis is tested on a retrospective, consecutively collected database of 204 patient-specific IAs. The first 119 cases are assigned to training and the remainder to testing dataset. An is calculated based on the pulsatility index ( PI ) approximated either from the literature or solving an optimization problem (denoted as PI ). Student's t -test and logistic regression (LR) are used for hypothesis testing and data fitting, respectively. RESULTS: An can significantly discriminate ruptured and unruptured status with 95% confidence level ( P < .0001). An (using PI ) and An (using PI ) significantly predict the ruptured IAs (for training dataset An\!: AUC = 0.85, An\!: AUC = 0.90, and for testing dataset An\!: sensitivity = 94%, specificity = 33%, An\!: sensitivity = 93.1%, specificity = 52.85%). CONCLUSION: An > 1 predicts ruptured status. Unlike traditional hemodynamic parameters such as wall shear stress and oscillatory shear index, An has a physical threshold of one (does not depend on statistical analysis) and does not require time-consuming flow simulations. Therefore, An is a simple, practical discriminator of IA rupture status.